Evidence for digenic inheritance in some cases of Antley-Bixler syndrome?. Issue 1 (1st January 2000) - Reardon, William; Smith, Anne; Honour, John W; Hindmarsh, Peter; Das, Debipriya; Rumsby, Gill; Nelson, Isabelle; Malcolm, Sue; Adès, Lesley; Sillence, David; Kumar, Dhavendra; DeLozier-Blanchet, Celia; et al.
Abstract : The Antley-Bixler syndrome has been thought to be caused by an autosomal recessive gene. However, patients with this phenotype have been reported with a new dominant mutation at the FGFR2 locus as well as in the offspring of mothers taking the antifungal agent fluconazole during early pregnancy. In addition to the craniosynostosis and joint ankylosis which are the clinical hallmarks of the condition, many patients, especially females, have genital abnormalities. We now report abnormalities of steroid biogenesis in seven of 16 patients with an Antley-Bixler phenotype. Additionally, we identify FGFR2 mutations in seven of these 16 patients, including one patient with abnormal steroidogenesis. These findings, suggesting that some cases of Antley-Bixler syndrome are the outcome of two distinct genetic events, allow a hypothesis to be formulated under which we may explain all the differing and seemingly contradictory circumstances in which the Antley-Bixler phenotype has been recognised.